2022
DOI: 10.3389/fimmu.2022.840857
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgE Levels Are Associated With the Prognosis of Minimal Change Disease

Abstract: BackgroundPrevious reports showed that some patients with minimal change disease (MCD) had high serum immunoglobulin E (IgE) levels. This study aimed to explore the proportion of MCD patients with high serum IgE levels and evaluate the correlation between serum IgE levels and MCD remission and relapse.MethodsThis study enrolled 222 new-onset patients with renal biopsy-confirmed MCD from October 2012 to October 2019 at the First Affiliated Hospital of Zhejiang University in Hangzhou, China. Patients’ demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Serum IgE was persistently and significantly higher in FRNS than IFRNS ( 23 ). In our study, it was found that the time to first relapse of MCD children in the high-IgE group was significantly shorter, which was consistent with other studies’ results ( 7 , 24 ). In addition, a higher percentage of MCD patients experienced FR in the high-IgE group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum IgE was persistently and significantly higher in FRNS than IFRNS ( 23 ). In our study, it was found that the time to first relapse of MCD children in the high-IgE group was significantly shorter, which was consistent with other studies’ results ( 7 , 24 ). In addition, a higher percentage of MCD patients experienced FR in the high-IgE group.…”
Section: Discussionsupporting
confidence: 93%
“…Serum IgE levels may not only reflect disease activity but may also implicate disease outcome in childhood of INS ( 5 , 6 ). A recent study reported that MCD patients with high-IgE levels were observed to prolong first reach disease remission and prone to early relapses ( 7 ). Fewer relevant studies have been performed in pediatric and biopsy-proven MCD patients about correlation between serum IgE levels and prognosis of MCD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found a strong relationship between renal disease and atopy accompanied by heightened serum IgE antibodies [18]. Lee et al [10] found that the serum IgE level increased in immunoglobulin A nephropathy patients with renal deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [10] found that the serum IgE level increased in immunoglobulin A nephropathy patients with renal deterioration. Another study indicated that the serum IgE level was an independent predictor of NS recurrence [18]. Likewise, Cheung et al [19] found higher IgE levels during NS relapse compared to remission.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Under normal conditions, serum IgE levels are generally low, and increased levels tend to coincide with allergic reactions. 15 The purpose of this report is to describe the advantages of total IgE screening for detecting mouthwash allergic reactions associated with recurrent erythema oral multiforme (ROEM).…”
Section: Introductionmentioning
confidence: 99%